Plutarhovo vzrokoslovje: Uvod v Rimska in Grška vprašanja - Sunčič, Maja (Monitor ISH, 2006)
The paper seeks to explain the neglect of Plutarch's Roman and Greek Questions, offering some topical suggestions for research. In the light of the recent scholarship, it proposes a re-reading of Roman Questions primarily from the aspect of otherness. Plutarch attempts to erase the differences between the Romans and Greeks through a complete Hellenisation of the former and a proposed "marriage" between the two peoples. This union is to result in a perfect blend, modelled on the mythological marriage of the Romans and the Sabine women. Plutarch's solution of otherness-engendered problems at the levels of marriage, state, and cosmos is a radical one: the fusion, blending, synkrasis, of opposites.
Keywords: Plutarchus, ok.46-ok.120; poroka; wedding; antični Rim; antična antropologija; religija; religion